2018
DOI: 10.1111/are.13671
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthetic efficacy and biochemical effects of 1,8-cineole in rainbow trout (Oncorhynchus mykiss , Walbaum, 1792)

Abstract: The aim of the present study was to investigate the anaesthetic efficacy and biochemical effects of 1,8-cineole (cineole) in rainbow trout (Oncorhynchus mykiss). The fish were exposed to 200, 300, 400, 500, 600 and 800 ll/L cineole and time of induction of anaesthesia and recovery from anaesthesia were recorded. Thereafter, the fish haematological and biochemical responses to anaesthesia with different concentrations of cineole were studies. Moreover, the haematological and biochemical response of fish anaesth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 62 publications
0
19
1
Order By: Relevance
“…There is no study reporting stress responses of fish to anaesthesia with either citronellal or linalool to make a precise comparison. However, Taheri Mirghaed, Ghelichpour, Zargari, and Yousefi () found no significant difference in blood stress markers of Oncorhynchus mykiss anaesthetized by either eugenol or 1,8‐cineole; but there was a tendency to increase in stress response in the eugenol‐anesthetized fish. Yousefi, Hoseini, et al () found no significant difference in plasma stress markers of common carp anaesthetized with either eugenol or thymol.…”
Section: Discussionmentioning
confidence: 99%
“…There is no study reporting stress responses of fish to anaesthesia with either citronellal or linalool to make a precise comparison. However, Taheri Mirghaed, Ghelichpour, Zargari, and Yousefi () found no significant difference in blood stress markers of Oncorhynchus mykiss anaesthetized by either eugenol or 1,8‐cineole; but there was a tendency to increase in stress response in the eugenol‐anesthetized fish. Yousefi, Hoseini, et al () found no significant difference in plasma stress markers of common carp anaesthetized with either eugenol or thymol.…”
Section: Discussionmentioning
confidence: 99%
“…Serum protein levels are indicators of fish health (Hoseini & Tarkhani, ; Hoseini, Hedayati, et al, ). Most of the fish serum proteins are synthetized in liver (Taheri Mirghaed, Ghelichpour, et al, ) and no change in their levels after ammonia challenge may suggest no adverse effects of the challenge on protein synthesis in common carp. However, it is necessary to determine serum protein electropherogram for better understanding of the effects of ammonia toxicity on serum proteins (Hoseini, Hedayati, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Cineole is a strong antioxidant (Batish et al, ) showing growth promotion and stress mitigating effects in Oncorhynchus mykiss (Hoseini, Taheri Mirghaed, Iri, & Ghelichpour, ; Taheri Mirghaed, Hoseini, & Ghelichpour, ). It is also used as anaesthetic in aquaculture (Mazandarani & Hoseini, ; Taheri Mirghaed, Ghelichpour, Zargari, & Yousefi, ). Studies have shown that cineole can mitigate toxic effects of xenobiotic (2,3,7,8‐tetrachlorodibenzo‐p‐dioxin) in mice (Ciftci, Ozdemir, Tanyildizi, Yildiz, & Oguzturk, ).…”
Section: Introductionmentioning
confidence: 99%
“…In common carp, anaesthesia with 400 ppm cineole within 460 seconds led to higher cortisol and glucose levels, compared with anaesthesia with 1000 ppm within 180 seconds (Hoseini et al, 2020). Such results have been obtained in rainbow trout; moreover, fast anaesthesia has induced less hypoxia in the fish (Taheri Mirghaed, Ghelichpour, Zargari, et al, 2018). Despite these studies, the current knowledge about anaesthetic effects of cineole in fish is scarce and limited to these species, which rises a need for study on other fish species.…”
mentioning
confidence: 78%
“…Although anaesthesia is a tool to mitigate stress during fish handling, it may cause stress by itself (Zahl et al, 2010). Previous studies have shown that anaesthesia with cineole significantly induces cortisol and glucose elevation in rainbow trout (Taheri Mirghaed, Ghelichpour, Zargari, et al, 2018) and common carp (Hoseini et al, 2020), and higher elevations were reported in the fish anaesthetized by lower cineole concentrations; it seems that the reason for such responses is time dependency of plasma cortisol and glucose.…”
Section: Discussionmentioning
confidence: 99%